Umrtnost a vzdelani v Ceske Republice - Sobotik, Z; Rychtarikova, J (Demografie, 1992)
The effect of educational status on mortality is explored using mortality data for regions in Czechoslovakia from the mid-1970s to the present. The data are analyzed and compared with trends in other European countries. (SUMMARY IN ENG AND RUS)
Keywords: Developed Countries; Demography; Europe, Eastern; Research; vyspělé země; mortalita; Comparative Studies; východní Evropa; populace; Population Dynamics; socioekonomické faktory; Economics; výzkum; Research Methodology; Economic Factors; Studies; Population; Europe; Mortality; Eastern Europe; Socioeconomic Factors; populační dynamika; Československo; společenská třída; Demographic Factors; ekonomika; Czechoslovakia; demografie; stupeň vzdělání; Social Class; Differential Mortality; Socioeconomic Status; Educational Status; Evropa